Comprehensive Management of Pregnancy with Anaemia - Aulia Ridla Fauzi; Rosidah Solihah; Resna Litasari; Fitria Andini; Neli Sunarni; Sri Utami Asmarani; Hani Septiani; Dini Ariani (Genius Journal, 2022)
Objective: The aim of this case study is to carry out comprehensive management for pregnant women with mild anemia. Method: The design is a case study design with comprehensive care. This case study uses an analytical descriptive method, with the main objective of exploring the problem, providing an overview of the case, and analyzing more deeply midwifery care according to the client's needs. Results: Comprehensive care carried out for pregnant women with anemia was successfully carried out by increasing HB levels and giving birth without complications, as well as the condition of the newborn in good condition. Conclusion: Oral iron (Fe) supplementation is the standard of care in obstetric practice in pregnancy. The increase in hemoglobin levels in pregnant women with mild anemia conditions can be increased by providing correct and effective information, monitoring Fe consumption regularly by midwives, nurses, and health workers for 30 days, and providing information on danger signs during delivery until the baby's condition is born.